Functional Javascript - Fogus, Michael, ....- (Sebastopol (Calif.) : O'Reilly Media, 2013)
How can you overcome JavaScript language oddities and unsafe features? With this book, you'll learn how to create code that's beautiful, safe, and simple to understand and test by using JavaScript's functional programming support. Author Michael Fogus shows you how to apply functional-style concepts with Underscore.js, a JavaScript library that facilitates functional programming techniques. Sample code is available on GitHub at https://github.com/funjs/book-source. Fogus helps you think in a functional way to help you minimize complexity in the programs you build. If you're a JavaScript programmer hoping to learn functional programming techniques, or a functional programmer looking to learn JavaScript, this book is the ideal introduction.
"Introducing Functional Programming with Underscore.js"--Cover.
Includes bibliographical references and index.
Keywords: JavaScript (Computer program language).; Functional programming (Computer science).